PHENOMENOLOGICAL RECEPTION OF WAR AS A HUMAN EXPERIENCE: THE EXAMPLE OF OCCUPATION - Amelchenko, Oleksandra (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
The article focuses on the conceptualization of the experience of occupation based on the phenomenological descriptions of life under occupation proposed by Maurice Merleau-Ponty and Jean-Paul Sartre. The philosophical potential of the phenomenological methodology is demonstrated by its use in critical war studies, which rethink this phenomenon from the perspective of human experience, rejecting the dominant approach to war as a continuation of politics by other means. Analyzing the research of the representative of critical studies of war, Shane Brighton, the phenomenological potential of the works of Carl von Clausewitz is revealed in the context of rethinking war as the excess of being over knowledge. It is also demonstrated how the understanding of war proposed by E. Levinas is used in interdisciplinary studies of this phenomenon to understand the impact of war on people's lives. At the same time, the author distinguishes between the reference to descriptions of war in works of literature and phenomenological works made by Sh. Brighton to generalize how war is experienced, and phenomenological descriptions of the experience of war itself. The consideration of the essays by M. Merleau-Ponty and J.-P. Sartre helps to demonstrate how the phenomenological methodology is used to describe the direct experience of war, particularly the experience of occupation. The article shows that the phenomenological approach allows not only to rethink war as a generative force, as S. Brighton does, but also to conceptualize specific experiences of war. Thus, using the examples of descriptions of life under occupation offered by M. Merleau-Ponty and J.-P. Sartre, it is shown that the experience of authentic life under occupation can be conceptualized as the experience of struggle in the ranks of the Resistance movement. The conducted research allows us to conclude that it is necessary to use phenomenology to achieve a truly human understanding of war, that is, to understand it as a phenomenon that confronts people with a choice to save their own lives as private individuals and live an illusory freedom or to participate in the Resistance movement and sacrifice their lives in the fight for the freedom of all citizens. The results obtained indicate the need for further phenomenological research of war experiences, which will involve the analysis not only of the experience of occupation, but also other forms of experiencing war.